Awareness Centered Learning as One of the Language Learning Models to Build the Good Character of Learners-based Innovative Creator in the Future - Sawirman Sawirman (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
Awareness Centered Learning (ACL) is a learning model developed to address the problems of students’ lack of awareness during the (language) learning process. The core objective of this model is to develop the internal awareness, good national character, and strong integrity of the students through focusing on authentic ideas and creativity building. This objective becomes the basis of ACL methodology in which the process is framed to be students’ self inflicted determination to contemplate, not only to think and to use. Contemplation on the objects of language learning material is the very ground of designing new authentic ideas and awareness which will shape more profound good character and integrity. ACL views language awareness in the context of learning English as a foreign language to be a mere means or instrument to master the knowledge in the western world, but not to be hegemonized or dominated mentally by Western centrism. Based on this point, the national character and identity to be shaped by ACL through learning English is to be equal to the westerns in producing authentic ideas. The purpose of this writing is to explore the history, concepts, indicators, methodology and philosophy including impact of ACL to TEFL and its contribution to the Indonesian character of education as well. This model had been disseminated in International TESOL Methods held by American English Institute of Oregon University during ten weeks since October 7 to December 13, 2013. ACL gained well reception from hundreds of participants around the world at that time.